2017
DOI: 10.1088/1361-6560/aa8c53
|View full text |Cite
|
Sign up to set email alerts
|

Avoiding nerve stimulation in irreversible electroporation: a numerical modeling study

Abstract: Electroporation based treatments consist in applying one or multiple high voltage pulses to the tissues to be treated. As an undesired side effect, these pulses cause electrical stimulation of excitable tissues such as nerves and muscles. This increases the complexity of the treatments and may pose a risk to the patient. To minimize electrical stimulation during electroporation based treatments, it has been proposed to replace the commonly used monopolar pulses by bursts of short bipolar pulses. In the present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 48 publications
(80 reference statements)
6
45
0
Order By: Relevance
“…However, a numerical study showed that the stimulation thresholds for nerve fibers are more than one order of magnitude larger in H-FIRE waveforms compared to 100 ls monopolar pulses. 26 The authors of that study attributed the divergent threshold dependences on the applied waveform to the geometrical differences between treated cells and nerve fibers which causes the latter to display significantly longer membrane charging times. As a consequence, despite requiring larger electric fields, H-FIRE protocols can largely reduce muscle contractions while maintaining treatment efficacy as shown in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a numerical study showed that the stimulation thresholds for nerve fibers are more than one order of magnitude larger in H-FIRE waveforms compared to 100 ls monopolar pulses. 26 The authors of that study attributed the divergent threshold dependences on the applied waveform to the geometrical differences between treated cells and nerve fibers which causes the latter to display significantly longer membrane charging times. As a consequence, despite requiring larger electric fields, H-FIRE protocols can largely reduce muscle contractions while maintaining treatment efficacy as shown in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…29,35,42,43,51 The electric fields required to kill cells with H-FIRE are significantly higher than in conventional IRE protocols, 38,39 but when moving from monopolar IRE waveforms to bipolar H-FIRE bursts, the excitation thresholds of peripheral nerves increase even more significantly than the thresholds for cell death. 26 Thus, it is possible to minimize muscle contractions while maintaining treatment efficacy with H-FIRE.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, shorter pulse durations require a higher voltage to achieve a similar ablation in healthy tissue if the other pulsing parameters are maintained; in malignant cells, H-FIRE selectivity seems to benefit from using higher frequency waveforms [38,[48][49][50]. The relationship between pulse width, cell kill, and tissue excitation has been modestly investigated [34,51], so future efforts to find the optimal pulsing parameters may prove beneficial for H-FIRE therapy. Future applications may utilize a current cage configuration to control or limit the zone of muscle/nervous stimulation, applying a precedent wherein a current cage was used to reduce the volume of tissue exposed to a 5 V/cm muscular excitatory threshold, instead of a two needle configuration [52].…”
Section: Discussionmentioning
confidence: 99%
“…However, different possible explanations were offered. It was suggested that (1) stimulation threshold raises faster than the threshold for irreversible electroporation with decreasing pulse length62 which is a consequence of geometrical differences between nerve fibers and tumor cells 63. (2) At around 1 μs there is an overlap of the depolarization threshold and electroporation threshold on the strength-intensity curve 41.…”
Section: Discussionmentioning
confidence: 99%